Design for Six Sigma in product and service development : applications and case studies - Cudney, Elizabeth A.; Furterer, Sandra L. (Boca Raton, FL. : CRC Press, 2012)
'Design for Six Sigma (DFSS) is a data-driven quality strategy for designing products and services. The goal of DFSS is to avoid process problems using systems engineering techniques. DFSS consists of five interconnected phases: Define, Measure, Analyze, Design, Verify. This book provides a detailed description of how to apply DFSS in product and service development. It provides instructional strategies, an overview of benefits and uses, and a roadmap that links several methodologies including organizational leadership, product development, system integration, critical parameter management, voice of the customer, quality function deployment, and concept generation'--
Includes bibliographical references and index.
Keywords: Six Sigma (Quality control standard).